PERAN STRES KERJA POSITIF (EUSTRESS) TERHADAP STRES KERJA PADA KARYAWAN : THE ROLE OF POSITIVE WORK STRESS (EUSTRESS) ON EMPLOYEE STRESS - Nadia Shafira; Fenty Zahara Nasution (Psikologi Prima, 2022)
Stress at work is something that often happens to employees. Most people are their own worst enemy when it comes to stress. They throw themselves into long hour, high stress jobs while simultaneously adding even more stress outside of work by needlessly stacking commitments and responsibilities that trap even more. This stress could have implications well if stresssors stimulate the levels that can be compensated, this is called eustress. Otherwise, if it is excessive, it can cause distress, then the role of eustress can help employees in dealing with work stress problems. This study aims to describe the role of eustress. The method used is a quaitaive method with a literature study method related to the role of work stress